Analisis SWOT strategi BMT dalam bersaing dengan Bank Umum Syariah di Indonesia: Studi literatur - Romadhoni, Ahmad Rizqi (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the strategies of Baitul Maal wat Tamwil (BMT) in competing with Islamic Commercial Banks (BUS) in Indonesia using the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. The research employs a literature review method by examining various previous studies published between 2015 and 2025 in both national and international journals. The findings reveal that BMT’s main strengths lie in its social proximity to communities, flexible financing schemes, and strong social orientation. Its weaknesses include limited capital, human resource capacity, and managerial competence. Externally, BMT has significant opportunities through the integration of cash waqf, regulatory support, and the rise of Islamic fintech, while threats arise from banking digitalization and unequal regulatory supervision. Based on these findings, the recommended strengthening strategies for BMT involve human resource development, governance improvement, and the adoption of digital innovations rooted in Islamic values. These strategies are expected to enhance BMT’s long-term competitiveness amid the rapid growth of Indonesia’s Islamic financial industry.